A study of building plan approval for extension and renovation work (individual application) / Ahmad Faisal Mohd Isa - Mohd Isa, Ahmad Faisal (Faculty of Architecture, Planning and Surveying, 2008)
The main objective of this research is to study about building plan approval procedure for extension or renovation work. This research focused on three different local authorities approach where are Kuala Lumpur City Hall (DBKL), Shah Alam City Council (MBSA) and Subang Jaya Municipal Council (MPSJ). An observation method and desktop study are used to understand the procedure building plan process for extension or renovation work. The case study involves on local authority which are DBKL, MBSA and MPSJ. The researcher have figure out a detail procedure and process from the application stage till the issuance of Letter of Permission. The set of questionnaires were distributed to occupant in term of to fulfill the second objective which is “7o recognize understanding o f occupant toward on procedure o f extension or renovation work”. While the interviews were set up with local authority to compare the step is taken to solve an illegal work exactly in extension or renovation work as fulfill of third objective.